Conceptions of Legitimacy Under International Human Rights Law and Islamic Rights Law - Nabeel, Raas (UI Scholars Hub, 2024)
Islamic law, or the shariah, is a rich body of legal rules and obligations that aims to protect individuals from wrongs committed to each other and wrongs committed to God. However, Islamic law is often considered to be at odds with international human rights law, particularly in certain domains such as gender rights, the freedom of expression, the freedom of religion, and the right to dignity. Muslim-majority States have criticized the Universal Declaration of Human Rights, the International Bill of Rights, as well as other international human rights conventions for the seeming incompatibility of their obligations with the rules, practices, and customs of the shariah that they are bound by. Muslim states have already lodged reservations and declarations against norms in certain conventions. However, in some cases, this has resulted in the complete abrogation of these of these norms, rather than a reserved application of them. This paper will examine the clash between international human rights law and human rights under Islamic law, with a particular focus on the aforementioned rights. I argue that said clash should not be used to undermine the legitimacy of either framework, but rather as the impetus to understand what makes the conceptions of each right individually legitimate. Ultimately, the paper will end in questioning whether the ‘universalism’ of international human rights law as a façade for ‘whatabouttery’ and virtue-signaling, as opposed to a genuine concern for consistent human rights law around the world.